Exploring the dust content of galactic winds with Herschel – II. Nearby dwarf galaxies. Issue 1 (13th March 2018) - McCormick, Alexander; Veilleux, Sylvain; Meléndez, Marcio; Martin, Crystal L; Bland-Hawthorn, Joss; Cecil, Gerald; Heitsch, Fabian; Müller, Thomas; Rupke, David S N; Engelbracht, Chad
Abstract : We present the results from an analysis of deep Herschel Space Observatory observations of six nearby dwarf galaxies known to host galactic-scale winds. The superior far-infrared sensitivity and angular resolution of Herschel have allowed detection of cold circumgalactic dust features beyond the stellar components of the host galaxies traced by Spitzer 4.5 $μ$ m images. Comparisons of these cold dust features with ancillary data reveal an imperfect spatial correlation with the ionized gas and warm dust wind components. We find that typically ∼10–20 per cent of the total dust mass in these galaxies resides outside of their stellar discs, but this fraction reaches ∼60 per cent in the case of NGC 1569. This galaxy also has the largest metallicity (O/H) deficit in our sample for its stellar mass. Overall, the small number of objects in our sample precludes drawing strong conclusions on the origin of the circumgalactic dust. We detect no statistically significant trends with star formation properties of the host galaxies, as might be expected if the dust were lifted above the disc by energy inputs from ongoing star formation activity. Although a case for dust entrained in a galactic wind is seen in NGC 1569, in all cases, we cannot rule out the possibility that some of the circumgalactic dust might be associated instead with gas accreted or removed from the disc by recent galaxy interaction events, or that it is part of the outer gas-rich portion of the disc that lies below the sensitivity limit of the Spitzer 4.5 $μ$ m data.